2005
DOI: 10.1186/1471-2296-6-51
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties associated with outpatient management of drug abusers by general practitioners. A cross-sectional survey of general practitioners with and without methadone patients in Switzerland

Abstract: BackgroundIn Switzerland, general practitioners (GPs) manage most of the patients receiving methadone maintenance treatment (MMT).MethodsUsing a cross-sectional postal survey of GPs who treat MMT patients and GPs who do not, we studied the difficulties encountered in the out-patient management of drug-addicted patients. We sent a questionnaire to every GP with MMT patients (556) in the French-speaking part of Switzerland (1,757,000 inhabitants). We sent another shorter questionnaire to primary care physicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
3
14
0
1
Order By: Relevance
“…Although the majority of those who responded believed that prescribing controlled drugs was part of general medical practice and drug users visiting the clinic would not affect other patients' access, 70% believed treatment should be provided centrally by specialists. This is similar to findings in other parts of the world 14,15 and could be attributed partially to a lack of confidence in the success of treating poly-drug users, a lack of guidelines or potential stigmatisation of this patient group.…”
Section: Discussionsupporting
confidence: 85%
“…Although the majority of those who responded believed that prescribing controlled drugs was part of general medical practice and drug users visiting the clinic would not affect other patients' access, 70% believed treatment should be provided centrally by specialists. This is similar to findings in other parts of the world 14,15 and could be attributed partially to a lack of confidence in the success of treating poly-drug users, a lack of guidelines or potential stigmatisation of this patient group.…”
Section: Discussionsupporting
confidence: 85%
“…[32] Previous studies have made some suggestions to overcome the reluctance in GPs to attend training are discussion groups on practical cases, community based nurse prescribing, and multidisciplinary collaboration. [11,26,33] From our results rose the idea of 'advisory physicians', GPs who are trained in OST management who provide advice to their colleague GPs whenever needed. This can be a timesaving solution and stimulate sharing of knowledge and experience amongst colleagues.…”
Section: Limitations Of the Studymentioning
confidence: 79%
“…[9,10] A Swiss study in 2005 indicated that only 23.9% of GPs were willing to accept new patients for OST. [11] From these results, we can assume that barriers remain to exist in GPs to accept OST patients in their general practice.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Des études ont essayé de les caractériser : l'isolement, le manque de temps ou de formations, les représentations négatives des toxicomanes ou alcooliques [4,[7][8][9]. Ils seraient davantage présents chez les MG que chez les psychiatres et les spécia-listes en addictions [7].…”
Section: Introductionunclassified